Emerging Natural-Product-Based Treatments for the Management of Osteoarthritis - Maria-Luisa; Annabelle Cesaro; Marija Mazor; Eric Esteve; Sabine Berteina-Raboin; Thomas M. Best; Eric Lespessailles; Hechmi Toumi (MDPI AG, 2021)
Osteoarthritis (OA) is a complex degenerative disease in which joint homeostasis is disrupted, leading to synovial inflammation, cartilage degradation, subchondral bone remodeling, and resulting in pain and joint disability. Yet, the development of new treatment strategies to restore the equilibrium of the osteoarthritic joint remains a challenge. Numerous studies have revealed that dietary components and/or natural products have anti-inflammatory, antioxidant, anti-bone-resorption, and anabolic potential and have received much attention toward the development of new therapeutic strategies for OA treatment. In the present review, we provide an overview of current and emerging natural-product-based research treatments for OA management by drawing attention to experimental, pre-clinical, and clinical models. Herein, we review current and emerging natural-product-based research treatments for OA management.